THE MAIN ROLE OF DELTA-9-TETRAHYDROCANNABINOL (THC) TO DOWNREGULATE AN EXPRESSION OF CANNABINOID 1 (CB1) RECEPTOR IN CANNABIS WITHDRAWAL SYNDROME - Qhabibi, Faqrizal Ria (Departemen Psikiatri Fakultas Kedokteran Universitas Brawijaya, 2025)
Introduction – Cannabinoids from Cannabis sativa have derived compounds that are the best characterized like delta-9-tetrahydrocannabinol (THC) and cannabidiol (CBD) as the main psychogenic compounds from Cannabis sativa. In addition, THC is an important agonist for the CB1 receptors and has a responsibility to develop cannabis withdrawal. This paper aims to reveal the role of delta-9-tetrahydrocannabinol (THC) to downregulate an expression of cannabinoid 1 (CB1) receptor and their correlation to developing cannabis withdrawal syndrome. Methods – A literature review evaluating the role of delta-9-tetrahydrocannabinol (THC) to downregulate the expression of CB1 receptors. The article search strategy is using a consort statement with the main keyword “Cannabinoid 1 (CB) Receptor”, “cannabis withdrawal syndrome (CWS)”, “Delta-9-tetrahydrocannabinol (THC)” to get structured and specific results. Data extracted from Science Direct, Springer Link, PubMed, Google Scholar databases and the only papers published from 2010-2021 that are included. Results – The author reviewed 21 articles that met inclusion criteria based on the consort statement. The psychoactive effect of cannabis results from the binding of delta-9-tetrahydrocannabinol (THC) to the CB1 receptor. Discuss – Based on some experiments, intensive exposure to THC can decrease the density of CB1 receptors in the tissue by downregulating their expression. A low density of CB1 receptor will suppress the mesolimbic dopamine function that has a main role in the development of cannabis withdrawal. Conclusion – Intensive exposure to delta-9-tetrahydrocannabinol (THC) as a psychogenic substance of cannabis able to downregulate the expression of the cannabinoid 1 (CB1) receptor. The decrease of CB1 receptor density in the brain is a consequence of the downregulation of CB1 receptor expression. Based on some experiments reveal that decreasing CB1 receptor density will affect to decrease of mesolimbic dopamine function which has a main role in the development of cannabis withdrawal.